2021
DOI: 10.1111/dme.14600
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium‐glucose transport protein 2 inhibitors on mortality and heart failure in randomized trials versus observational studies

Abstract: Aim Randomized clinical trials (RCTs) allocating type 2 diabetes patients to treatment with sodium‐glucose transport protein 2 (SGLT‐2) inhibitors or placebo have found significant effects on the risk of heart failure and modest effects on mortality. In the wake of the first trials, a number of observational studies have been conducted, some of these reporting a mortality reduction of 50% compared to active comparators. In this review, we systematically assess and compare the results on all‐cause mortality, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Despite reducing doses, the benefits accrued from using SGLT2is remained strong. Third, we could not avoid indication and time-related biases where those patients prescribed SGLT2is tend to have better predefined outcomes [ 40 , 41 ]. The systematic differences in baseline characteristics between treatment-exposed and unexposed groups departed from what we usually observed in RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reducing doses, the benefits accrued from using SGLT2is remained strong. Third, we could not avoid indication and time-related biases where those patients prescribed SGLT2is tend to have better predefined outcomes [ 40 , 41 ]. The systematic differences in baseline characteristics between treatment-exposed and unexposed groups departed from what we usually observed in RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also supports the findings of previous meta-analyses of observational studies, which showed that SGLT2 inhibitors are associated with reduced odds/risk of heart failure events compared with people treated with other glucose-lowering medications. However, three of the previous analyses did not stratify included studies by the presence of baseline CVD, [62][63][64] while another only reported risk for studies with populations with 20%-30% incidence of CVD. 65 Our review includes more recently published studies, across more countries, which provides more data on high and low cardiovascular risk groups, making it possible for us to explore differences between these groups more comprehensively.…”
Section: Discussionmentioning
confidence: 99%